Kindness is my superpower : a children's book about empathy, kindness and compassion - Ortego, Alicia ([s.n.] : [Alicia Ortego], 2020)
Lucas learns about the importance of kindness.
2.1
K-3.
K-3
Keywords: Compassion -- Juvenile fiction; Empathy -- Juvenile fiction; Kindness -- Juvenile fiction; Compassion -- Fiction; Empathy -- Fiction; Kindness -- Fiction; Compassion -- Fiction; Empathy -- Fiction; Kindness -- Fiction; Picture books